Detraining effects in college football players during the competitive season - Schneider, V.; Arnold, B.; Martin, K.; Bell, D.; Crocke, P. (The Journal of Strength and Conditioning Research, 1998)
This study investigated detraining effects in 28 college football players during a 16-week competitive season. The subjects were divided into either a linemen group or a non-linemen (all other players) group to determine whether the player`s position might influence detraining. The players were tested immediately before and after the in-season on a series of practical, football related field tests and on specific lab tests for isokinetic strength (shoulder abduction and leg extension), anaerobic capacity, and aerobic power. The field test results showed significant decreases in the bench press for both groups and significant decreases in flexibility and vertical jump for the non-linemen group. The standing long jump and 20-yard shuttle run showed decreases in performance for both groups, although the results were not statistically significant. Maximal anaerobic capacity basically remained unchanged while aerobic power increased by almost 6%.